Sludge water: a potential pathway for the spread of antibiotic resistance and pathogenic bacteria from hospitals to the environment - Zhao, Bingxuan; Zhang, Rui; Jin, Baolin; Yu, Zuozhou; Wen, Weicheng; Zhao, Tong; Quan, Yue; Zhou, Jingya (Frontiers in Microbiology, 2025)
Hospitals play an important role in the spread of antibiotic resistance genes (ARGs) and antimicrobial resistance (AMR). The ARGs present in hospital wastewater tend to accumulate in activated sludge, with different ARGs exhibiting varying migration rates. As a result, sludge water produced during the activated sludge treatment process may be a significant source of ARGs entering the environment. Despite this, research into the behavior of ARGs during sludge concentration and dewatering remains limited. This study hypothesizes that ARGs might exhibit new behaviors in sludge water during sludge concentration. Using metagenomic analysis, we explored the distribution and migration risks of ARGs and human pathogenic bacteria (HPB) in sludge water, comparing them with those in hospital wastewater. The findings reveal a strong correlation between ARGs in sludge water and hospital wastewater, with subtypes such as arlR, efpA, and tetR showing higher abundance in sludge water. Although the horizontal gene transfer potential of ARGs is greater in hospital wastewater than in sludge water, the resistance mechanisms and migration pathways are similar even when their HPB host associations differ. ARGs in both environments are primarily transmitted through coexisting mobile genetic elements (MGEs). This suggests that sludge water serves as a critical route for the release of hospital-derived ARGs into the environment, posing potential threats to public health and ecological safety.